CONGESTION CONTROL AND LOAD BALANCED ROUTING IN WIRELESS AD HOC NETWORKS USING OPTIMIZATION TECHNIQUES - HABIB, IFFAT (2015)
Ad hoc networks consist of mobile devices such as mobile phones, tablets, laptops, that are connected over a wireless medium Most of the existing routing protocols for wireless ad hoc networks follow the shortest path or minimum distance as the route selection criteria. This type of routing is called shortest path routing (SPR). However, the shortest path does not balance the traffic load on all nodes in a network. When multiple users use the shortest path for data transfer, some nodes may be overloaded with data forwarding and the wireless links get more data traffic than they can handle. The congestion can be decreased by careful distribution of data traffic on all available links. This technique is called load-balancing. Existing literature on load-balancing considers certain parameters for congestion measurement.